Confirmatory Factor Analysis untuk Mengetahui Pemanfaatan Multimedia Learning pada Perguruan Tinggi Swasta di Kota Semarang - Achmad Solechan; Fitro Nur Hakim (Jurusan Teknologi Informasi Universitas Semarang, 2014)
Dominant indicator of the use of multimedia in learning needs to be studied using the Confirmatory Factor Analysis. This study aims to determine the most dominant factor affecting the use of multimedia in learning, this study uses the Technology Acceptance Modelling theory. This study uses the technique of Judgment Sampling Area or a sampling technique that is based on the determination of the research area. Determination of the study area are four private universities in Semarang, namely USM, Udinus, STMIK Provisi and Unisbank, so the overall number of respondents as many as 200 students. This study shows that: 1-the greatest contribution value of the Perceived Usefulness latent variable that is multimedia learning increase the effectiveness of learning in the classroom, 2-the greatest contribution value of the Confirmation latent variable, that is Lecturer Services using multimedia learning is preferred, 3-the greatest contribution value of the Perceived Ease of Use latent variable that is teaching materials using multimedia learning is something that is easy for students to understand. This study also shows that : 4-the greatest contribution value of the Satisfaction latent variable that is multimedia learning used by Lecturer in teaching and learning in the classroom is able to provide information in accordance with the information that students need, and 5-the greatest contribution value of the Continued IT Usage Intention latent variable that is students interested in understanding the material, which is taught by Lecturer, if Lecturer teaching using multimedia based than conventional models